Gamification and Participation: The Power of Live Broadcasting - Palomino-Flores, Paola (2024)
The study explores gamification in digital marketing, focusing on live broadcasts through a quantitative approach. Supported by surveys of 250 viewers, it objectively assesses how gamified strategies enhance audience participation and commitment, and influence brand recognition. Findings show that gamification boosts audience engagement by 40% and brand retention by 30%. Additionally, 60% are more inclined to purchase after live interaction. Challenges include the need for precise brand alignment and flawless user experience. Risks of diverting attention with poor gamification execution and potential fatigue from market saturation are noted. This analysis underscores overcoming technical and creative obstacles to fully harness gamification’s power, enhancing engagement and improving conversion rates.